Dietary advanced glycation end products and cancer risk in Japan: From the Takayama study. Issue 8 (25th June 2022) - Wada, Keiko; Nakashima, Yuma; Yamakawa, Michiyo; Hori, Akihiro; Seishima, Mitsuru; Tanabashi, Shinobu; Matsushita, Shogen; Tokimitsu, Naoki; Nagata, Chisato
Abstract: Few large epidemiological studies have evaluated the association between dietary advanced glycation end products (AGEs) and cancer risk. We evaluated the relationship between dietary AGE intake and the incidence of total cancer and site‐specific cancers in a population‐based prospective study in Japan. Participants were 14, 173 men and 16, 549 women who were 35 years of age or older in 1992. Dietary intake was assessed via a validated food frequency questionnaire. Intake of the AGE N ε ‐carboxymethyl‐lysine (CML) was estimated using databases of CML content in foods determined using ultraperformance liquid chromatography–tandem mass spectrometry. Cancer incidence was confirmed through regional population‐based cancer registries. During a mean follow‐up period of 13.3 years, 1954 men and 1477 women developed cancer. We did not observe a significant association between CML intake and the risk of total cancer in men or women. In men, compared with the lowest quartile of CML intake, the hazard ratios of liver cancer for the second, third, and highest quartiles were 1.69 (95% CI: 0.92–3.10), 1.48 (95% CI: 0.77–2.84), and 2.10 (95% CI: 1.10–3.98; trend p  = 0.04). Conversely, a decreased relative risk of male stomach cancer was observed for the second and highest quartiles of CML intake versus the lowest quartile, with hazard ratios of 0.73 and 0.67, respectively (trend p  = 0.08). Our finding on the potential harmfulness of consuming AGEs on liver cancer risk is intriguing and warrants further study. Abstract : A high intake of advanced glycation end products Nε‐carboxymethyl‐lysine was associated with an increased risk of liver cancer in Japanese men. Our finding suggests the potential harmfulness of consuming advanced glycation end products on liver cancer risk.